Práctica axiológica educativa y su incidencia en el proceso de enseñanza aprendizaje de los estudiantes de básica intermedia de la escuela “Otto Arosemena Gómez” período lectivo 2014- 2015". Plan de capacitación. - Salazar Merelo, Emma (2016)
This research was conducted at the School of Basic Education "Otto Arosemena", located at Av. Jaime Roldós and the eighteenth in the canton Quevedo Los Rios Province, to meet the educational reality in terms of axiological education practice, selected for the implementation of the research sample they were interviewed the Director; survey of ten teachers in selected grades, 199 students from fourth to seventh basic and 175 representatives. Factors that influence the behavior of students of the School of Basic Education "Otto Arose Mena" are the low rates of applicability of values and little tolerance among peers that comes together to create hostile environments and desmejorando the teaching to improve their Personal formation. The most important values that should be practiced in the educational community are respect and companionship to improve teaching activities and also apply it in their daily lives and that students achieve build knowledge more easily, developing and implementing values. The student behavior affects the teaching-learning process, as a percentage annoys his colleagues, affecting the normal development of educational activities in the classroom; improving this context may be more easily learn when teachers allow them to operate more freely, using values such as respect, learning will be more meaningful. It requires a plan for teacher training in educational axiológica in terms of improving student comprehensive training for mastery and application of axiológicas practices by teachers, such as group work, problem solving, discovery of new knowledge will contribute to students can test and develop their level of respect for their colleagues and to the teachers also get better performance in learning process as well as for teachers are the key tools for better performance in the classroom.